The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1016/j.esxm.2020.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Desire for Parenthood and Associated Trends in Czech Lesbian Women

Abstract: Introduction Worldwide, there are more lesbians who chose to have children in the context of a same-sex relationship than ever before. The Czech studies focusing on this issue, including the analysis of methods of conception, are limited. Aim We aimed to examine the changes over time in the desire of Czech lesbian women for children and to analyze their chosen methods of conception. Methods We analyzed retrospectively the personal history of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 25 publications
1
1
0
3
Order By: Relevance
“…To compare, the general desire for parenthood was 87.2% in German and 92.3% in Chinese participants in a study sampling 13498 students (40). Similar to our results, a study on Czech lesbians sampled between 2013 and 2017 indicated that 15.6% of the participants did not desire parenthood (41). In a study from the United States, 52.0% of gay men and 41.0% of lesbian women without children reported wanting to become a parent (42).…”
Section: Discussionsupporting
confidence: 78%
“…To compare, the general desire for parenthood was 87.2% in German and 92.3% in Chinese participants in a study sampling 13498 students (40). Similar to our results, a study on Czech lesbians sampled between 2013 and 2017 indicated that 15.6% of the participants did not desire parenthood (41). In a study from the United States, 52.0% of gay men and 41.0% of lesbian women without children reported wanting to become a parent (42).…”
Section: Discussionsupporting
confidence: 78%
“…Gay men therefore might be less likely from the very outset to give any consideration to the idea of becoming a parent. A study by a private healthcare facility [Turcan et al 2020] mapping the increase in the desire to become a parent among lesbian women after registered partnerships were introduced in the legislation (in 2006) showed that lesbian women often adopt the strategy of having 'a fictitious partner'. This strategy is a way for lesbian women to legally undergo IVF.…”
Section: Discussionmentioning
confidence: 99%
“…I když musí gayové a lesby v Česku stále ještě překonávat celou řadu legislativních, společenských a ekonomických bariér na cestách k rodičovství, pro řadu z nich už není založení homoparentální rodiny nemyslitelné, jak ukázaly již i předchozí studie z nedávné doby (např. Kadlecová a Kutálková 2020; Turčan et al 2020;Nešporová 2021). Neznamená to, že by mezi lidmi s neheterosexuálními identitami k tranzicím do rodičovství v rámci partnerství mužů a žen nedocházelo.…”
Section: Diskuse a Závěrunclassified
“…V praxi však lesby kliniky asistované reprodukce s fiktivními partnery využívají (např. Turčan et al 2020). Náhradní mateřství (surogace, kdy žena porodí -zpravidla jí geneticky cizí -dítě páru, který se stává dítěti rodičovským) v ČR sice zakázáno není, česká legislativa ho ale ani přímo neřeší (Honzová et al 2020).…”
unclassified